Perceptions About Brand Image and Promotion on Consumer Purchase Decisions in the Indonesian Home Education Parenting Program at Pt Naruna Karya Bersama - Noviansyah, Kafita Yogi; Dewanti, Mentari Clara (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine perceptions regarding